WISATA BUDAYA, IRAW TENGKAYU UPADA MEMPERKENALKAN KOTA TARAKAN MELALUI BUDAYA ADAT IRAW TENGKAYU: Abstrak - Salim, Valdesta Rashendy; Astina, I Komang; Sumarmi, Sumarmi (Universitas Negeri Surabaya, 2023)
The city of Tarakan also has interesting customs and cultures of the community, such as the traditional ceremony of Iraw Tengkayu, which is one of the cultures of the city of Tarakan and comes from the Tidung tribe. Tarakan City is a city that has great tourism potential, but obstacles in the form of a lack of information, exposure, and facilities make it difficult to develop this potential. This study aims to explore the efforts that can be made to introduce the City of Tarakan through cultural tourism and the Iraw Tengkayu traditional ceremony. The method used is descriptive, with data obtained through literature studies. The results of this study indicate that the efforts made to introduce the tourism sector in Tarakan City through Iraw Tengakyu are carried out through improving tourist attractions, increasing digital promotions, and enhancing collaboration and community participation. This is done to increase tourist interest, create positive images and perceptions through the original culture of Tarakan City, and influence the decision-making process and preferences of tourist destinations.